Design and Development of Pd‐Catalyzed Aerobic N‐Demethylation Strategies for the Synthesis of Noroxymorphone in Continuous Flow Mode. Issue 4 (1st February 2017) - Gutmann, Bernhard; Cantillo, David; Weigl, Ulrich; Cox, D. Phillip; Kappe, C. Oliver
Abstract : Strategies for the generation of noroxymorphone from 14‐hydroxymorphinone are presented. Noroxymorphone is the key intermediate in the synthesis of various opioid antagonists, including naloxone, naltrexone, and nalmefene, as well as mixed agonists‐antagonists such as nalbuphine. The transformation requires removal of the N ‐methyl group from the naturally occurring opiates and double‐bond hydrogenation. The pivotal reaction step thereby is an N ‐methyl oxidation with colloidal palladium(0) as catalyst and pure oxygen as terminal oxidant. The reaction produces a 1, 3‐oxazolidine intermediate, which can be readily hydrolyzed to the corresponding secondary amine. Different reaction sequences and the use of various phenol protecting groups were explored. The most direct route consumes only H2, O2, and H2 O as stoichiometric reagents and produces only H2 O as a byproduct. Challenges inherent to gas/liquid reactions with oxygen as oxidant have been addressed by developing a continuous flow process. Abstract : The generation of noroxymorphone from 14‐hydroxymorphinone by N ‐demethylation/hydrogenation has been explored. The crucial reaction step is a continuous‐flow N ‐methyl oxidation with colloidal palladium(0) as catalyst and pure oxygen as the stoichiometric oxidant.